The Do Not Call registry - CHIK, Warren B. (Institutional Knowledge at Singapore Management University, 2014)
The adoption of the Personal Data Protection Act has transformed the legal regime for data protection in Singapore. This book explains the history and evolution of data protection in Singapore, highlights issues that will need to be worked out in practice as the new law is implemented and derives lessons that may be taken from other countries in the region and beyond. Bringing together leading scholars and practitioners in the field, the book will be of interest to the academic, legal and business communities. Key questions considered in the book include how to reconcile notions of privacy in an information age, and how national laws can regulate an increasingly interconnected world. Highlights – diverse perspectives on data protection – explores the complexity of issues surrounding personal data protection – highlights potential issues post-implementation of the new law – draws on lessons from the experience of other jurisdictions